POTENSI EKSTRAK KASAR ENZIM BROMELIN PADA BONGGOL NANAS (Ananas comosus) SEBAGAI KOAGULAN ALAMI LATEKS (Hevea brasiliensis) - Santi, Fitri; Restuhadi, Fajar; Ibrahim, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimed at discovering the optimum concentration of crude extracts of pineapple as natural latex coagulant and determining the effect of crude extracts of bromelain enzyme on the quality of coagulum produced. The research was mainly conducted at the Laboratory of PT. Riau Crumb Rubber Factory, in May and July 2016. The study used a completely randomized design (CRD). The design consists of 6 treatments of coagulant substance with 3 times repetitions with the result that 18 experimental units were gathered. The data were analyzed using analysis of variance (ANOVA), and were they found significant, Duncan's New Multiple Range Test (DNMRT) at the level of 5% was further used. The results of the study showed that the optimum concentration obtained is by adding K2 (1,5% crude extracts of pineapple with enzymes activated). The addition of complete enzyme crude extract of pineapple proved to significantly affect the pH value, dry rubber content, ash content, dirt content, however the values of Po and PRI.Keywords: coagulant, bromelain enzymes, pineapple